Artful Dementia Film 2021 - Mittner, Lilli; Grøn, Tiia; Bergli, Terje (Zenodo, 2020)
In this short film we share aesthetic perspectives on how to connect in co-creative spaces. The film production is based on a set of video recordings collected within the Artful Dementia Research Lab: http://www.uit.no/research/adlab - at UiT The Artic University of Norway. The film presents visual representations of in-the-moment experiences and brings together voices from sociology, applied theatre, music, fine arts, and practitioners participating in a larger citizen science project in Northern Norway. The film was shot during the kick-off session of the project ‘Shorelines’ at Bergsodden residential care home in February 2020. All those who wanted to participate had been informed about the broad outline of the project, and that the whole session would be filmed. All participants, and legally authorized representatives (next of kin) when needed, gave informed and proxy consent in advance. Furthermore, we collected consent by editing and watching the film together with the residents and their next of kin who all agreed orally to publish it publicly and make it available for researchers and others who work to change perceptions of dementia. ® Artful Dementia Research Lab / RESULT at UiT The Artic University of Norway 2021 Citation: Mittner, Lilli; Bergli, Terje; Grøn, Tiia: Artful Dementia Film. UiT The Arctic University of Norway, 2021. #artsbasedresearch #citizenscience #dementia #connectivity #socialchange #situatedartintervention #relationalmodel